Optical measurement, characterization and quantification for plastic deformations and stress in three-dimensional structures: Recent developments, challenges, and prospects. (December 2021) - Ju, Yang; Xing, Dongyi; Mao, Lingtao; Ren, Zhangyu; Chiang, Fu-pen
Highlights: Optical methods for measuring and quantifying plastic phenomena are reviewed. Optical methods ensure full-field and real-time measurement and characterization. Optical methods with 3D printing are promising for visualizing plastic phenomena. Efficient algorithms and high-precision smart optical devices are future directions. Abstract: Plastic deformations and the associated stress evolution are closely related to the destruction of diverse engineering structures. Accurate measurement, characterization, quantification, and visualization of plastic deformations and the associated stress are critical to the evaluation and prediction of the failure of engineering structures. To date, various optical methods have been developed to explore plasticity-related phenomena. However, it is challenging for traditional optical methods to accurately characterize, quantify, and visualize the plastic deformation and associated stress in three-dimensional (3D) structures. In this article, we review the recent developments of digital image correlation, digital volume correlation, moiré methods, optical interferometry, and photoelastic techniques in terms of measurement, characterization, and visualization of plasticity-related phenomena in materials. The challenges and prospects of combining optical techniques with promising 3D printing to improve the efficiency and accuracy in 3D measurement, characterization, quantification, and visualization of plastic deformations and the associated stress in complex 3D structures are discussed.